Reflections on Learning, Life and Work
XVIII, 284 p.
Keywords: This book records the stories of doctoral study experiences of the twenty-two writers. These research degree experiences are embedded in the lives and careers of the writers and the twenty-two distinctive projects draw from those individual lives and careers. The authors write about meeting the continuing demands of older and younger family members and of their struggles with ill health and work place demands while working through their studies. There is also the joy of coming to see themselves and being seen as research scholars and supporting and celebrating with others as they move through candidature proposals and ethics applications to graduation. Apart from the stories that bring the writers to their particular projects and that colour their individual journeys, storying methodology is most often selected for the research, all of which is undertaken within the arts, humanities and education. Phenomenology, narrative, ethnography are central to most of the studies and the detailed accounts of each research topic, methods and outcomes locate each of the research projects in rich bodies of knowledge. Valued writers and readers in these fields, Mary Beattie and Elaine Martin have read each reflection and provided in turn a foreword and an afterword which bookend the volume and further enrich these reflections on learning, life and work.